Calculation of bending deflection and stresses of a pipe with flowing fluid in the case of variable ground load - Didžgalvis, Rimantas; Sudintas, Antanas; Tiknevičienė, Irena (Lietuvos matematikos rinkinys, 1999)
The mathematical model of the oscillations of fulfilled pipe is formed on the case when that pipe suddenly losses the support. Using the methods of approximate solutions of differential equations, the analytical pipe bend dynamic expressions were given at the case, when the ground load minimises exponentially. Finally, those solutions could be used for the finding more exact normal tensions in the wall of the pipes, when the reological parameters of the ground are determined.